Stability Improvement for Three-Phase Grid-Connected Converters Through Impedance Reshaping in Quadrature-Axis - Fang, Jingyang; Li, Xiaoqiang; Li, Hongchang; Tang, Yi (IEEE transactions on power electronics, 2018)
Three-phase AC-DC and DC-AC power converters have been extensively employed as grid-interfaces in various applications, e.g., distributed generation and energy storage systems. In these applications, power converters should always synchronize with the mains grid so that active and/or reactive power can properly be regulated while maintaining desired waveforms of grid currents. Grid synchronization necessitates accurate information of grid voltages, which is normally obtained through phase-locked-loops (PLLs). However, the employment of PLLs may bring in stability concerns. Previous research revealed that the inclusion of PLLs shapes the impedance of power converters into a negative resistance in the quadrature-axis (q-axis), and this should be responsible for instability. To resolve the instability issue caused by PLLs, this paper proposes an impedance controller for reshaping the q-axis impedance into a positive resistance in the low-frequency band. Without any extra burden on system hardware, the proposed controller can easily be implemented by directly relating the q -axis voltage to the q-axis current reference. As a result, the presented three-phase power conversion system can operate stably even under a severely weak grid condition, which are verified by simulation and experimental results.